Pengaruh Manajemen dan Kepemimpinan Dosen terhadap Hasil Belajar Mahasiswa - Syaifullah, Lasyatta; Maksum, Hasan; Purwanto, Wawan; Rifdarmon, Rifdarmon; Arpan, Muhamad (Juwara: Jurnal Wawasan dan Aksara, 2024)
This research aimed to analyze the correlation of lecturer management and leadership in organizing and administering the learning process on student learning outcomes in the Sensors and Transducers course. The research method used a quasi-experimental with a non-equivalent group design. The research population consisted of 107 students divided into 4 classes and the research sample consisted of 30 students, comprising 15 students from class A and 15 students from class B. Purposive sampling was the technique used in determining the research sample. Based on the suggestions from the course lecturer, class A was the control class and class B was the experimental class. The data collection technique used documentation, with the data collection tool being student learning outcomes documents. The data analysis technique used the t-test. The research results showed that the learning outcomes in class B were higher than in class A. Based on these research results, it can be concluded that the application of management strategies and the lecturer's leadership in the Sensors and Transducers course effectively improved student learning outcomes. The implications of the research results focus on the application of management strategies in the learning process should be a concern for lecturer so that student learning outcomes can be achieved optimally. In addition, lecturer leadership should also be demonstrated in the learning process so that student learning outcomes can be achieved according to learning objectives.